Digital Translanguaging: Harnessing Technology to Foster Intercultural Competence in Multilingual Educational Contexts - Ethan Tan; Siri Lek; Ton Kiat (Journal Emerging Technologies in Education, 2025)
Background. The increasing globalization of education has resulted in more diverse, multilingual classrooms, highlighting the need for intercultural competence alongside language proficiency. Translanguaging, a practice where learners utilize their entire linguistic repertoire to communicate, offers a potential framework for fostering this competence. With the rise of digital tools, the practice of digital translanguaging has emerged, enabling students to navigate and interact across multiple languages using technology. Purpose. This study investigates how digital translanguaging, facilitated by technology, can foster intercultural competence in multilingual educational settings. It aims to explore the impact of digital tools in promoting both language proficiency and cultural awareness, providing students with the skills to communicate. Method. A mixed-methods approach was employed, combining pre- and post-test surveys to measure language proficiency and intercultural competence, alongside qualitative interviews and focus groups to explore students' experiences with digital translanguaging tools. Results. The findings indicate significant improvements in both language proficiency (23% increase) and intercultural competence (24% increase) in the experimental group using digital translanguaging tools. Students reported enhanced engagement and a deeper understanding of cultural diversity. Conclusion. Digital translanguaging tools effectively enhance both language learning and intercultural competence, suggesting that technology can play a pivotal role in multilingual education.